Procedures for the Control and Use of Firearms for Members of the Police of the Republic of Indonesia - Dudy, Aryadi Almau; Ashady, Suheflihusnaini (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
The police institution serves as the spearhead in realizing the nation's ideals of justice, civility, and peace. This is regulated by Law No. 2 of 2003 concerning the police, where the police institution is one of the government's functions in maintaining security, public order, law enforcement, protection, guidance, and services to the community.To support these functions and duties, police officers are granted the authority to use firearms to achieve the nation's goals. In using firearms, the police institution must comply with applicable regulations and prioritize human rights (HR). This research aims to understand the system of granting possession and use of firearms permits for Indonesian police officers. This study employs normative legal research methods, which focus on the provisions of laws and regulations and their application in legal events. The sources of legal materials used consist of literature and field research. Literature includes legal materials obtained from reading literature and official sources in legal research, while field research is obtained by conducting interviews with informants.